"How is cognitive remediation training perceived by people with schizophrenia? A qualitative study examining personal experiences". (3rd May 2016) - Contreras, Natalia A.; Lee, Stuart; Tan, Eric J.; Castle, David J.; Rossell, Susan L.
Abstract: Background : Meta-analytical findings have shown Cognitive Remediation (CR) effectiveness in augmenting cognitive and functional outcomes. Comparatively, a minimum amount of qualitative evidence has been reported to date. Aims : This study aimed to explore the subjective experience of participants undertaking a CR trial. Method : Twenty people with schizophrenia completed a questionnaire-facilitated interview, after having completed 20 h of CR. Thematic analysis was then used to identify codes and themes. Results : Three themes were identified. In relation to reported benefits, all participants found the training to be a positive experience, with 70% having identified cognitive improvements, 45% improved motivation or confidence and 20% improved social skills. The role of the cognitive trainer in being supportive, adaptive and instructive was consistently reported as important, and most participants commented positively about the group format. Fewer participants had observed a transfer to real life settings, with improved social skills, use of cognitive strategies or aspects of everyday living reported by 40% of participants. Conclusions : These data highlight that all participants reported participation in CR to be a positive experience, with many reporting observed benefits following participation. Key aspects of the training that contributed to this positive experience were also identified and may assist in the further development of this intervention.